Calanthe × yarlungzangboensis, a new natural hybrid in genus Calanthe (Orchidaceae) from China - Wu, Po-Po; Wang, Zi; Jia, Ning-Xia; Guo, Shi-Wei; Liu, Chang-Cheng; Jin, Xiao-Hua; Guo, Ke (Phytotaxa, 2021)
Calanthe × yarlungzangboensis P. P. Wu & Z. Wang, a new natural hybrid was described and illustrated from Xizang, China. Calanthe griffithii and C. tricarinata were considered as putative parentage by morphological traits and molecular data from nrITS and two plastid DNA (rbcL and matK). Calanthe × yarlungzangboensis is easily distinguished from its parentage by mid-lobe with three tuberculatus lamellae. The new hybrid grows in subalpine evergreen coniferous forest dominated by Tsuga dumosa in the eastern Himalayas with elevation about 2500m.